MEMOTIVASI DIRI DENGAN HAL-HAL KECIL SEDERHANA DALAM USAHA MENINGKATKAN PRESTASI OLAHRAGA - Ahadin., Ahadin (Jurnal Pesona Dasar, 2020)
Behaviors and actions of individuals to achieve a goal to be obtained in principle are largely determined by a desire, needs, and expectations. Individuals in conducting behavior, actions, and actions are always based on factors that are nature coming from within themselves or coming from outside themselves or from the environment. Factors from within the individual can determine behavior, actions and actions, as well as factors from outside the individual can strengthen or reduce the motive of an individual in acting, acting and doing. Motive is a stimulus, encouragement, desire, or desire of individuals to behave, act and act. While motivation refers to the process that encourages individuals to behave, act and act in reacting to each situation, thus the motive is a driving force for behavior, actions and actions. In the competition in every sport the highest level is generally followed by athletes who have great talent, have amazing talents, are persistent, highly disciplined, have a strong and tough mentality, so what distinguishes the champion or who has amazing achievements with ordinary achievements are very difficult to distinguish. At this very high level of achievement, an athlete with small, simple self-motivated techniques that are very well managed can make the athlete successful in his career.Â